The Role of the Pacific‐Antarctic Ridge in Establishing the Northward Extent of Antarctic Sea‐Ice - A. I. Ferola; Y. Cotroneo; P. Wadhams; G. Fusco; P. Falco; G. Budillon; G. Aulicino (Geophysical Research Letters, 2023)
Abstract Monitoring the Antarctic sea‐ice is essential for improving our knowledge of the Southern Ocean. We used satellite sea‐ice concentration data for the 2002–2020 period to retrieve the sea‐ice extent (SIE) and analyze its variability in the Pacific sector of the Southern Ocean. Results provide observational evidence of the recurring formation of a sea‐ice protrusion that extends to 60°S at 150°W during the winter season. Furthermore, we discuss how the Pacific‐Antarctic Ridge (PAR) influences this phenomenon. Our findings show that the northward deflection of the southern Antarctic Circumpolar Current front is driven by the PAR and is associated with the enhanced sea‐ice advance. The PAR also constrains eddy trajectories, limiting their interaction with the sea‐ice edge. These factors, within the 160°W–135°W sector, cause an average SIE increase of 61,000 km2 and 46,293 km2 per year more than the upstream and downstream areas, respectively.